In silico molecular interaction between human lung surfactant protein-D and silica nanoparticles - Muta Tah Hira, 1982-, author 641574 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Sarjana Sains (Biosains)) - Universiti Teknologi Malaysia, 2016